Multi-criteria optimization of disk tillage implements with adjustable elastic shanks by substantiating design and operating parameters - Kozachenko, Oleksii; Козаченко, Олексій Васильович; Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Dyakonov, Sergey; Дьяконов, Сергій Олександрович; Pakhuchyi, Andrii; Пахучий, Андрій Миколайович; Volkovskii, Oleksandr; Волковський, Олександр Михайлович; Luts, Pavlo; Луц, Павло Михайлович (Sumy State University, 2026)
The research presents numerical and experimental investigations of a disk working element mounted on an elastic shank with a stiffness regulator. Using numerical simulation in SolidWorks, the distributions of stresses and deformations in the shank, their amplitude-frequency characteristics, and the influence of geometric parameters and disk orientation angles on system performance were determined. The analysis showed that the maximum absolute deformations at the disk attachment point and frame connection vary between 0.12 and 0.38 mm, while the maximum stresses in the shank and stiffness regulator range from 85 to 240 MPa, depending on design parameters. The optimal shank parameters ensured vibration stability in different directions and effective interaction between the disk and the soil, minimizing energy consumption and providing uniform surface tillage. Experimental tests conducted in a soil bin confirmed the patterns of variation in the draft force acting on the frame and on individual points of the shank, the vibration frequency of the working element, and soil compaction depending on the disk penetration depth, the travel speed of the implement, and the angle of the wedge-shaped insert. The results enabled the determination of rational operating parameters for the disk element that achieve an optimal balance between energy efficiency, stability of dynamic regimes, and soil tillage quality. The frame draft force varied in the range of 430–780 N, while local forces at the shank reached 310–690 N and 280–640 N, respectively. The vibration frequency of the working element was observed within 50–63 Hz. The results showed that the soil compaction coefficient ranged from 0.44 to 0.72, with a reduction of up to 39 % under optimal conditions. Overall, the proposed methodology combines numerical modeling with full-scale experiments, enabling comprehensive optimization of the design and technological characteristics of disk implements. The use of adjustable elastic shanks increases soil tillage efficiency, reduces draft resistance, and improves soil structure formation, making the proposed design suitable for modern resource-saving agricultural technologies. У дослідженні представлено чисельні та експериментальні дослідження дискового робочого органа, встановленого на пружній стійці з регулятором жорсткості. За допомогою чисельного моделювання в SolidWorks визначено розподіли напружень і деформацій у стійці, їх амплітудно-частотні характеристики, а також вплив геометричних параметрів і кутів орієнтації диска на роботу системи. Аналіз показав, що максимальні абсолютні деформації в точці кріплення диска та з’єднання з рамою змінюються в межах 0,12–0,38 мм, тоді як максимальні напруження у стійці та регуляторі жорсткості становлять 85–240 МПа залежно від конструктивних параметрів. Оптимальні параметри стійки забезпечили вібраційну стійкість у різних напрямках та ефективну взаємодію диска з ґрунтом, мінімізуючи енергоспоживання і забезпечуючи рівномірний обробіток поверхні. Експериментальні випробування, проведені в ґрунтовому каналі, підтвердили закономірності зміни тягового опору, що діє на раму та окремі точки стійки, частоти коливань робочого органа та ущільнення ґрунту залежно від глибини заглиблення диска, швидкості руху агрегату та кута клиноподібної вставки. Отримані результати дозволили визначити раціональні режими роботи дискового органа, які забезпечують оптимальний баланс між енергоефективністю, стабільністю динамічних режимів і якістю обробітку ґрунту. Тягове зусилля на рамі змінювалося в межах 430–780 Н, тоді як локальні зусилля на стійці досягали відповідно 310–690 Н і 280–640 Н. Частота коливань робочого органа знаходилася в межах 50–63 Гц. Результати показали, що коефіцієнт ущільнення ґрунту змінювався в межах 0,44–0,72 із зниженням до 39 % за оптимальних умов. Загалом запропонована методика поєднує чисельне моделювання з натурними експериментами, що забезпечує комплексну оптимізацію конструктивних і технологічних параметрів дискових знарядь. Використання регульованих пружних стійок підвищує ефективність обробітку ґрунту, зменшує тяговий опір і покращує формування структури ґрунту, що робить запропоновану конструкцію придатною для сучасних ресурсоощадних агротехнологій.
Багатокритеріальна оптимізація дискових ґрунтообробних знарядь із регульованими пружними стійками шляхом обґрунтування конструктивних і експлуатаційних параметрів
Keywords: improved soil structure; покращена структура ґрунту; draft force reduction; зниження тягового опору; vibration stability; вібраційна стійкість; experimental study; експериментальне дослідження; numerical simulation; чисельне моделювання